# Math

posted by .

Use a counter example to show that cos(x+y)= cosx +cosy is not an identity

• Math -

Let x=π/4, y=π/4,
cos(x+y)
=cos(π/4+π/4)
=cos(π/2)
=0
cos(x)+cos(y)
=cos(π/4)+cos(π/4)
=√2/2+√2/2
=√2
Since √2 ≠ 0,
cos(x+y) ≠ cosx +cosy

## Similar Questions

1. ### Math

Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant help you (cscX-cotX)=1/sinX - cosX/sinX = (1-cosX)/sinX If you square this you have (1-cosX)^2/(sinX)^2 Now use (sinX)^2 = 1 - (cosX)^2 to get (1-cosX)^2 / 1 - …
2. ### Trig

prove the identity (sinX)^6 +(cosX)^6= 1 - 3(sinX)^2 (cosX)^2 sinX^6= sinx^2 ^3 = (1-cosX^2)^3 = (1-2CosX^2 + cos^4) (1-cosX^2) then multiply that out 1-2CosX^2 + cos^4 - cosX^2 + 2cos^4 -cos^6 add that on the left to the cos^6, and …
3. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
4. ### Math help again

cos(3π/4+x) + sin (3π/4 -x) = 0 = cos(3π/4)cosx + sin(3π/4)sinx + sin(3π/4)cosx - cos(3π/4)sinx = -1/sqrt2cosx + 1/sqrt2sinx + 1/sqrt2cosx - (-1/sqrt2sinx) I canceled out -1/sqrt2cosx and 1/sqrt2cosx Now …
5. ### Math

Use a counter example to show that cos(x+y)= cosx +cosy is not an identity
6. ### Math - Pre- Clac

Prove that each of these equations is an identity. A) (1 + sinx + cos x)/(1 + sinx + cosx)=(1 + cosx)/sinx B) (1 + sinx + cosx)/(1 - sinx + cosx)= (1 + sin x)/cosx Please and thankyou!
7. ### math

sinx+ siny/ (cosx+cosy)= tan 1/2 (x+y) prove this identity
8. ### Trigonometry

Write equivalent equations in the form of inverse functions for a.)x=y+cos è b.)cosy=x^2 (can you show how you would solve) a.) x= y+ cos è cos è = x-y theta = cos^-1(x-y) b.) cosy=x^2 cos(y) = x^2 y = Cos^-1(x^2)
9. ### Geometry

Find 2 cos(x/2) sin(x/2) when x = -π/6. I know that cos(x/2) = +- sqrt(1-cosx)/2 and sin(x/2) = +- sqrt(1+cosx)/2, but how to use this identity I'm not entirely sure. Please help.
10. ### Math

Suppose f(x) = sin(pi*cosx) On any interval where the inverse function y = f –1(x) exists, the derivative of f –1(x) with respect to x is: a)-1/(cos(pi*cosx)), where x and y are related by the equation (satisfy the equation) x=sin(pi*cosy) …

More Similar Questions